Comparison between Two-Dimensional and Three-Dimensional Assessments of the Fetal Corpus Callosum: Reproducibility of Measurements and Acquisition Time - Pomar, Léo; Baert, Jonathan; Mchirgui, Ali; Lambert, Véronique; Carles, Gabriel; Hcini, Najeh; Baud, David; Vial, Yvan (Journal of Pediatric Neurology, 2021)
The objective of this article was to study the reproducibility and reliability of the fetal corpus callosum measurements between two-dimensional (2D) and three-dimensional (3D) acquisitions. This prospective study enrolled 475 fetuses, monitored between 18 and 38 weeks of gestation by two operators. Starting from a transcerebellar axial plane, 3D and 2D mid-sagittal views of the corpus callosum were obtained. Measurements of length and thickness were performed and underwent quality control by independent reviewers. The acquisition time of the two methods was measured. Means, differences, and linear correlations were analyzed using t-test, regression and Pearson's correlation coefficients, and Bland–Altman's plots. This analysis was performed for each operator to test the interobserver reproducibility. Among the 432 cases measured using both methods, 380 (88%) were validated by quality control. The mean corpus callosum length and thickness were essentially the same using 2D and 3D measurements (2D: 33.8 ± 8.7 vs. 3D: 33.7 ± 8.7 mm, 2D: 2.2 ± 0.4 vs. 3D: 2.2 ± 0.4 mm, respectively; mean ± standard deviation [SD]). Linear regression coefficients and Pearson's coefficients were similar for length (2D: 0.8283 and 0.9191 vs. 3D: 0.8271 and 0.9095), but slightly different regarding thickness (2D: 0.6775 and 0.8231 vs. 3D: 0.5831 and 0.7636). Differences between 2D and 3D measurements, considering Bland–Altman's plots and correlated with gestational age, were acceptable (2D: 0.097 ± 0.559 mm, 3D: 0.004 ± 0.111 mm). The acquisition time required was significantly lower for 3D acquisitions (3D: 25.2 ± 14.5 seconds vs. 2D: 35.1 ± 19.4 seconds, p < 0.01). Linear regression and Pearson's coefficients for the measurements of corpus callosum length and thickness using 2D or 3D acquisitions did not differ between the operators. This study confirmed good reproducibility of corpus callosum assessment by transabdominal 3D acquisitions. The good feasibility in routine scans may lead to better screening for callosal dysgenesis.
Keywords: corpus callosum; 3D ultrasound; screening; neurosonography; callosal dysgenesis